Effect of microwave heat hardening on microstructure and strength of coke composed iron ore pellet. (2020) - Prasad, Rakesh; Venugopal, R.; Kumarswamidhas, L.A.; Pan, S.K.
Abstract: Iron ore pellets are used as feed stock of blast furnace with lump and sinter. Due to their uniform size range, uses ore fines, good physical properties. During the production of pellets, green ball with coke powder mix heated to get mechanical strength by conventional heating and microwave heating has been incorporated in this paper. The effect of both type of heating over strength (CCS) and surface morphology was studied to investigate the appropriate key variables for industrial application. Microstructure formation during both types heating process has been investigated by SEM and phase occurrence and quantitative analysis has been done for reduction by product by XRD technique. The results reveal that the reduction temperature and time depend on method of heating. The finer and porous structure were obtained with microwave heating which promote reducibility of product and conventional heating support the pellets strength for its physical properties.